Self-regulated learning: information and communication technologies (ict) and reading in higher education (Revista Electrónica REDINE, 2020)
The purpose of this article is to reflect on the process of self-regulation of learning and analyze the convenience and / or need to discuss the importance of this process in educational contexts, within the framework of the socialization of knowledge and the use of Information and Communication Technologies (ICT). We expose the review of some investigations that show data on the components of the process of self-regulation of learning, as well as proposals for its implementation in academics spaces that involve the use of new technologies is exposed. Particularly, we focus on the self-regulation of reading to exemplify and describe some components of regulatory process of learning, motivation, and selection of information and the elaboration of academic knowledge, reflected in academic performance of higher education student. Concludes whit the analysis of aspects in which the studies analyzed match particularly we highlight the figure of teacher as a mediator for the self-management of student learning.
Keywords: self-regulation; higher education student; reading self-regulation; technologies